The Neoproterozoic evolution of the western Siberian Craton margin: U-Pb-Hf isotopic records of detrital zircons from the Yenisey Ridge and the Prisayan Uplift - Priyatkina, N.; Collins, Bill; Khudoley, A.; Letnikova, E.; Huang, H. (Elsevier BV, 2018)
We present new LA ICP-MS U-Pb-Hf detrital zircon data from Neoproterozoic sedimentary basins located along the south-western margin of the Siberian Craton. In the Yenisey Ridge (the Taseeva basin), siliciclastic sedimentary units contain abundant 2.7–2.5 Ga, 2.0–1.75 Ga and 0.95–0.57 Ga detrital zircon populations, whereas for the Prisayan Uplift slightly different detrital zircon ages of 3.0–2.5 Ga, 2.2–1.8 Ga and 0.95–0.65 Ma are common. Mid Neoproterozoic sandstones were deposited in a rift setting or along a rifted cratonic margin facing a back-arc basin, whereas the immature to submature upper Ediacaran to Lower Cambrian fluvial successions were probably deposited in the foredeep setting, at the expense of proximal Neoproterozoic igneous suites and the underlying metasedimentary basement. A range of εHf values from −10 to +14 indicates intense mixing between juvenile and evolved magma components in a continental arc setting at ca. 950–570 Ma. Geological evidence, persistent input of detrital zircon material derived from ancient crustal units of western Siberian cratonic margin and evolution of Hf isotopic compositions suggest that the Neoproterozoic arc system of the Yenisey Ridge and, partly, Sayan orogens developed along the active margin of Siberia. In the Neoproterozoic, the arc system probably extended along the periphery of Rodinia into the Taimyr orogen of northern Siberia and Valhalla orogen of north-eastern Laurentia.